The status of three little known names proposed by Miranda-Ribeiro (1926) and the synonymization of Pyrrhura snethlageae Joseph & Bates, 2002 (Psittaciformes: Psittacidae: Arinae) - Gaban-Lima, Renato; Raposo, Marcos A. (Zootaxa, 2016)
The presence of complex geographic variation among species allied to the absence of clear morphological breaks among populations has led to many poorly defined taxa in the genus Pyrrhura (Psittacidae: Arinae: Arini). This article addresses nomenclature of the Pyrrhura picta species complex, particularly the identity of three little-known names introduced by Miranda-Ribeiro (1926): Pyrrhura luciani ochrotis, P. l. pallescens and P. l. melanoides. We show that these names represent subjective synonyms of Pyrrhura snethlageae Joseph & Bates, 2002. Furthermore, we argue that Pyrrhura pallescens (Miranda-Ribeiro, 1926) n. comb. should be considered as the valid senior name because: (1) there is no doubt about the type locality (near the type locality of P. snethlageae) and, as a consequence, it “will best serve stability and universality of nomenclature” as recommended by the International Code of Zoological Nomenclatural, and; (2) it corresponds to the most common phenotype usually referred to as P. snethlageae, the species name that has been used for bird specimens from this region. Those considering P. snethlageae lucida Arndt, 2008 as a valid taxon should refer to this population as Pyrrhura pallescens lucida (Arndt, 2008) n. comb. In a near future P. pallescens melanoides (Miranda-Ribeiro, 1926) n. comb. is likely to be considered the best senior synonym of P. p. lucida given its type locality (Teles Pires River, MT).